PENGARUH JENIS PELARUT TERHADAP AKTIVITAS ANTIOKSIDAN EKSTRAK ECENG PADI (Monochoria vaginalis Burm F. C. Presel.) - Padmawati, Ida Ayu Gede; Suter, I Ketut; Hapsari Arihantana, Ni Made Indri (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 9 No 1 (2020): Jurnal ITEPA, 2020)
This study was conducted to determine the effect of different solvents on the antioxidant activity of rice hyacinth extract and to find out the right type of solvent used to extract rice hyacinth with the highest antioxidant activity. The experimental design used in this study was a completely randomized design with various types of solvents as a treatment using maceration method. The treatment consisting of four type of solvents i.e water, ethanol, methanol, and acetone. All treatments were repeated four times to obtained 16 experimental units. The data obtained were analyzed by variance and if the treatment had significant effect then followed by Duncan test. The results showed that the various types of solvent treatments had a very significant effect (P<0.01) on antioxidant activity. The results showed that ethanol solvent had the best treatment which produced an antioxidant activity based on IC 50 of 0,49 mg/mL, yield of 26.17%, total phenol content of 11.12 mg GAE/g, total flavonoid content of 8.26 mg QE/g, total tannin content of 5.18 mg TAE/g. Keywords: rice hyacinth, maceration, anioxidant activity